2023
DOI: 10.3389/fendo.2023.1181856
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin does not impact the blunted counterregulatory response to recurrent hypoglycemia in mice

Abstract: IntroductionRecurrent episodes of insulin-induced hypoglycemia in patients with diabetes mellitus can result in hypoglycemia-associated autonomic failure (HAAF), which is characterized by a compromised response to hypoglycemia by counterregulatory hormones (counterregulatory response; CRR) and hypoglycemia unawareness. HAAF is a leading cause of morbidity in diabetes and often hinders optimal regulation of blood glucose levels. Yet, the molecular pathways underlying HAAF remain incompletely described. We previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Indeed, in the same study, the authors investigated the potential role of ghrelin in HAAF using ghrelin knockout mice and ghrelin cell-selective insulin receptor knockout mice and found that the counterregulatory responses (plasma glucagon and adrenaline) were reduced in both strains similar to the C57Bl/6N mice after recurrent hypoglycaemia. In a similar fashion, plasma ghrelin was also blunted in both the single and recurrent insulin injection groups [89]. The authors concluded that ghrelin deletion or elevation did not affect blood glucose or counterregulatory hormone responses, suggesting that ghrelin does not play a role in HAAF [89].…”
Section: The Effects Of 2dg and Insulin On Adrenaline Release In Huma...mentioning
confidence: 87%
See 4 more Smart Citations
“…Indeed, in the same study, the authors investigated the potential role of ghrelin in HAAF using ghrelin knockout mice and ghrelin cell-selective insulin receptor knockout mice and found that the counterregulatory responses (plasma glucagon and adrenaline) were reduced in both strains similar to the C57Bl/6N mice after recurrent hypoglycaemia. In a similar fashion, plasma ghrelin was also blunted in both the single and recurrent insulin injection groups [89]. The authors concluded that ghrelin deletion or elevation did not affect blood glucose or counterregulatory hormone responses, suggesting that ghrelin does not play a role in HAAF [89].…”
Section: The Effects Of 2dg and Insulin On Adrenaline Release In Huma...mentioning
confidence: 87%
“…In a similar fashion, plasma ghrelin was also blunted in both the single and recurrent insulin injection groups [89]. The authors concluded that ghrelin deletion or elevation did not affect blood glucose or counterregulatory hormone responses, suggesting that ghrelin does not play a role in HAAF [89].…”
Section: The Effects Of 2dg and Insulin On Adrenaline Release In Huma...mentioning
confidence: 87%
See 3 more Smart Citations